Mixed-integer linear programming framework for max-min power control with single-stage interference cancellation - Karipidis, Eleftherios; Yuan, Di; Larsson, Erik G. (2011 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2011)
We consider a wireless network comprising a number of mutually-interfering links. We study the transmit power control problem that determines the egalitarian signal-to-interference-plus-noise ratio under a novel setup. Namely, we assume that the receivers have multiuser detection capability, which enables decoding and cancellation of the interference, when it is strong enough. Determining the interference terms that can be cancelled is a combinatorial problem, which is intertwined with the power control problem. We propose a mixed-integer linear programming framework that jointly solves these problems optimally, using off-the-shelf algorithms. We illustrate with a simulation result the merit of the novel approach against the conventional one that precludes interference cancellation.